A rheumatoid arthritis patient complicated with adenine phosphoribosyltransferase deficiency and unilateral renal agenesis: a first case report. Issue 1 (2nd January 2017) - Matsubara, Erika; Yoshikawa, Noritada; Hosono, Osamu; Baba, Hiroyuki; Eri, Toshiki; Uehara, Masaaki; Oda, Aya; Sekita, Chieko; Taniguchi, Atsuo; Tanaka, Hirotoshi
Abstract: A 40-year-old woman with unilateral renal agenesis (URA) and a history of urolithiasis was diagnosed with rheumatoid arthritis (RA). Her arthritis was refractory to methotrexate (MTX) and she developed urolithiasis twice within two years. For refractory RA and recurrent urolithiasis, she was admitted to our hospital. She showed typical RA manifestations and administration of adalimumab successfully ameliorated her symptoms. Moreover, we revealed that her recurrent urolithiasis was caused by adenine phosphoribosyltransferase (APRT) deficiency, which is a rare autosomal recessive inherited metabolic disorder leading to renal stones, crystal nephropathy and renal failure. For prevention of recurrence of urolithiasis and those complications, we immediately treated her with a xanthine oxidase inhibitor febuxostat and urolithiasis has not relapsed without any side effects of febuxostat with MTX and adalimumab for more than a year. This is a first case report of RA patient complicated with URA and APRT deficiency. Since renal involvements often worsen prognosis and hamper aggressive immunosuppressive treatment for RA, immediate diagnosis and treatment of such rare but treatable extra-articular involvements contribute to better management of RA. Recently, since epistatic gene interactions are going to be known to account for the susceptibility of certain diseases, this case might be of genetic importance to consider the role of URA and APRT in RA.